The central administration of the executive power of the Republic of Bulgaria – an unreformed part of the state apparatus system - Nikolova, Raina (Law Journal of New Bulgarian University, 2022)
The present study is dedicated to the essence of the concept of “state apparatus”, to the historical and legal analysis of the formation of the central administrations of the executive power in Bulgaria and its development until the adoption of the current Constitution of the Republic of Bulgaria of 1991. It deals with the legal framework concerning the status of the national central public administration and criticizes its shortcomings. The study presents the development of the central public administration over a period of 30 years (1991–2021).